2022
DOI: 10.1155/2022/9538051
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Antigallbladder Carcinoma Activity Analysis of a New Nanometer Drug Delivery System Based on Data Acquisition

Abstract: In order to solve the problem of the application of data acquisition in the new nanometer drug delivery system of microscope, a research of antigallbladder carcinoma activity analysis was proposed. Gallbladder carcinoma (GBC) is a common malignant tumor in biliary tract diseases. Due to the lack of specific clinical manifestations in the early stage, GBC has the shortcomings of the hidden onset, the difficult diagnosis, and the high misdiagnosis rate. GBC ranks in the top position among the most common tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%